A randomised interventional trial of ω-3-polyunsaturated fatty acids on endothelial function and disease activity in systemic lupus erythematosus. Issue 6 (17th September 2007) - Wright, S A; O'Prey, F M; McHenry, M T; Leahey, W J; Devine, A B; Duffy, E M; Johnston, D G; Finch, M B; Bell, A L; McVeigh, G E
Abstract : Objective: To determine the clinical effect of dietary supplementation with low-dose ω-3-polyunsaturated fatty acids on disease activity and endothelial function in patients with systemic lupus erythematosus. Methods: A 24-week randomised double-blind placebo-controlled parallel trial of the effect of 3 g of ω-3-polyunsaturated fatty acids on 60 patients with systemic lupus erythematosus was performed. Serial measurements of disease activity using the revised Systemic Lupus Activity Measure (SLAM-R) and British Isles Lupus Assessment Group index of disease activity for systemic lupus erythematosus (BILAG), endothelial function using flow-mediated dilation (FMD) of the brachial artery, oxidative stress using platelet 8-isoprostanes and analysis of platelet membrane fatty acids were taken at baseline, 12 and 24 weeks. Results: In the fish oil group there was a significant improvement at 24 weeks in SLAM-R (from 9.4 (SD 3.0) to 6.3 (2.5), p<0.001); in BILAG (from 13.6 (6.0) to 6.7 (3.8), p<0.001); in FMD (from 3.0% (−0.5 to 8.2) to 8.9% (1.3 to 16.9), p<0.001) and in platelet 8-isoprostanes (from 177 pg/mg protein (23–387) to 90 pg/mg protein (32–182), p = 0.007). Conclusions: Low-dose dietary supplementation with ω-3 fish oils in systemic lupus erythematosus not only has a therapeutic effect on disease activity but also improves endothelial function and reduces oxidative stress and may therefore confer cardiovascular benefits.